2016
DOI: 10.1128/jvi.01272-16
|View full text |Cite
|
Sign up to set email alerts
|

Acute Simian Varicella Virus Infection Causes Robust and Sustained Changes in Gene Expression in the Sensory Ganglia

Abstract: Primary infection with varicella-zoster virus (VZV), a neurotropic alphaherpesvirus, results in varicella. VZV establishes latency in the sensory ganglia and can reactivate later in life to cause herpes zoster. The relationship between VZV and its host during acute infection in the sensory ganglia is not well understood due to limited access to clinical specimens. Intrabronchial inoculation of rhesus macaques with simian varicella virus (SVV) recapitulates the hallmarks of VZV infection in humans. We leveraged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 155 publications
(134 reference statements)
4
25
0
Order By: Relevance
“…As described for VZV, we and others have demonstrated that SVV primarily infects T cells that traffic to the ganglia as early as 3 days postinfection (Ouwendijk et al, 2013;Arnold et al, 2016a). Moreover, we showed that T cells isolated from the broncho-alveolar lavage (BAL) during acute infection supported SVV replication (Arnold et al, 2016a). These data firmly establish the importance of T cells in SVV pathogenesis making this model ideal for investigating how VZV infection alters T cell behavior and function.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…As described for VZV, we and others have demonstrated that SVV primarily infects T cells that traffic to the ganglia as early as 3 days postinfection (Ouwendijk et al, 2013;Arnold et al, 2016a). Moreover, we showed that T cells isolated from the broncho-alveolar lavage (BAL) during acute infection supported SVV replication (Arnold et al, 2016a). These data firmly establish the importance of T cells in SVV pathogenesis making this model ideal for investigating how VZV infection alters T cell behavior and function.…”
Section: Introductionsupporting
confidence: 77%
“…This model mimics the key characteristics of VZV infection including the development of varicella, cellular and humoral immune responses, the establishment of latency in sensory ganglia, and reactivation (Messaoudi et al, 2009;Mahalingam et al, 2010;Mahalingam et al, 2007;Kolappaswamy et al, 2007). As described for VZV, we and others have demonstrated that SVV primarily infects T cells that traffic to the ganglia as early as 3 days postinfection (Ouwendijk et al, 2013;Arnold et al, 2016a). Moreover, we showed that T cells isolated from the broncho-alveolar lavage (BAL) during acute infection supported SVV replication (Arnold et al, 2016a).…”
Section: Introductionsupporting
confidence: 58%
“…We also compared changes in gene expression in ganglia collected from animals that experienced a reactivation event and those that did not relative to ganglia collected from naïve animals (Arnold et al , 2016). Overall, we detected 967 DEGs (403 up-regulated, 325 down-regulated) in ganglia from animals that did not have a reactivation and 1200 DEGs (641 up-regulated, 559 down-regulated) in the ganglia from animals that did.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies from our lab have shown a down-regulation of neuronal genes during acute infection (Arnold et al , 2016), therefore we compared the DEGs detected after acute SVV infection (100 dpi) and those detected after SVV reactivation. Only 48 common DEGs were identified, most of which were down-regulated after both acute infection and reactivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation